How much protein can the body use in a single meal for muscle-building? Implications for daily protein distribution - Schoenfeld, B. J.; Aragon, A. A. (Journal of the International Society of Sports Nutrition, 2018)
Controversy exists about the maximum amount of protein that can be utilized for lean tissue-building purposes in a single meal for those involved in regimented resistance training. It has been proposed that muscle protein synthesis is maximized in young adults with an intake of ~ 20-25 g of a high-quality protein; anything above this amount is believed to be oxidized for energy or transaminated to form urea and other organic acids. However, these findings are specific to the provision of fast-digesting proteins without the addition of other macronutrients. Consumption of slower-acting protein sources, particularly when consumed in combination with other macronutrients, would delay absorption and thus conceivably enhance the utilization of the constituent amino acids. The purpose of this paper was twofold: 1) to objectively review the literature in an effort to determine an upper anabolic threshold for per-meal protein intake; 2) draw relevant conclusions based on the current data so as to elucidate guidelines for per-meal daily protein distribution to optimize lean tissue accretion. Both acute and long-term studies on the topic were evaluated and their findings placed into context with respect to per-meal utilization of protein and the associated implications to distribution of protein feedings across the course of a day. The preponderance of data indicate that while consumption of higher protein doses (> 20 g) results in greater AA oxidation, this is not the fate for all the additional ingested AAs as some are utilized for tissue-building purposes. Based on the current evidence, we conclude that to maximize anabolism one should consume protein at a target intake of 0.4 g/kg/meal across a minimum of four meals in order to reach a minimum of 1.6 g/kg/day. Using the upper daily intake of 2.2 g/kg/day reported in the literature spread out over the same four meals would necessitate a maximum of 0.55 g/kg/meal. Abstract from author